Peran Mikrobiom pada Sifilis - Benedikta Lauda; Ammarilis Murastami (Jurnal Ners, 2026)
Syphilis is a chronic sexually transmitted infection caused by Treponema pallidum, which can progress to neurosyphilis when it affects the central nervous system. Recently, the role of the human microbiome, the community of microorganisms living in the body has gained attention in understanding the pathogenesis of syphilis. The genital microbiota, particularly those dominated by Lactobacillus, help maintain mucosal balance and protect against infection. Imbalance in the microbiota, or dysbiosis, such as a decrease in Lactobacillus and an increase in anaerobic bacteria like Prevotella and Gardnerella, has been shown to raise the risk of sexually transmitted infections, including HIV and syphilis. In women, Lactobacillus maintains an acidic vaginal pH and suppresses inflammation, while the dominance of anaerobic bacteria can trigger proinflammatory cytokine production that promotes pathogen colonization. In men, a penile microbiota rich in anaerobes has also been linked to a higher risk of infection. Recent studies suggest that alterations in the gut microbiota may contribute to the progression of neurosyphilis, with increased Akkermansia levels associated with immune activation and inflammation. The complex interaction between the microbiome, immune system, and T. pallidum influences disease progression and treatment response. A deeper understanding of this relationship may lead to new strategies for preventing and managing syphilis..